2016
DOI: 10.1108/ijchm-07-2014-0374
|View full text |Cite
|
Sign up to set email alerts
|

Spa market segmentation according to customer preference

Abstract: Purpose – This paper aims to segment spa customers based on their preferences for a set of spa attributes. With the considerable growth rate of the spa market, it is vital for spa professionals to understand spa-goers’ preferences. However, academics and industry professionals have not devised a structured method by which to manage spa customers. Design/methodology/approach – A survey was conducted using a face-to-face survey with visito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…It helps the managers effectively discover the customers' satisfaction level from their services and detect their choice preferences [40]. Previous studies on customers' segmentation and preference prediction are mainly developed through survey data [47]. However, it is found that the use of machine learning techniques can be more effective in big data analysis and customer segmentation [48].…”
Section: Discussionmentioning
confidence: 99%
“…It helps the managers effectively discover the customers' satisfaction level from their services and detect their choice preferences [40]. Previous studies on customers' segmentation and preference prediction are mainly developed through survey data [47]. However, it is found that the use of machine learning techniques can be more effective in big data analysis and customer segmentation [48].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding hot spring tourism, consumers visit hot spring resorts with different purposes depending on their different regions [35]. A study showed that the consumers in Asia often pursue their personal inner peace (or peace of mind), so they pay more attention to seeking escape [36], a soothing experience [21,37], and tranquility [38], while in Western countries, visitors always focus on social factors in spas [21]. To reflect the strong customer demand, there is also a wide range of different types of service features or characteristics among establishments.…”
Section: Hot Springs Tourism Studiesmentioning
confidence: 99%
“…Under mass exploitation, researchers gradually became concerned with the comprehensive evaluation of exploiting hot spring resources. With the increasing awareness of the value of spa treatments, people began to attach importance to the commercial and economic value of hot springs, particularly the tourism industry, mainly for the behavior and demand characteristics of tourists [18], travel motivations [36,38,42,43], the geographical characteristics of customer marketing [15], as well as visitors' evaluation of spa experiences [44]. In addition to focusing on the value of hot spring resources, researchers later began to discuss the influencing factors of hot spring tourism development, such as hot spring hot brand [45], the coordinated development of the entire region's economy, and ecology at the external macro level [12,15,46,47], while other scholars studied the advantages and disadvantages of hot spring resorts with case analyses [12], focused on services and activities at hot spring destinations [48][49][50], and service quality and consumer preferences [15,22,35,48].…”
Section: Hot Springs Tourism Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was due to spas focusing on medical care (Smith and Puczkó, 2010) and the good standard of medical services rendered. In this segment, greater emphasis is typically placed on factors such as medicinal waters, medical assistance and staff (Alén et al, 2006), as opposed to the wellness segment, the preferences of which have been defined by Denizci Guillet and Kucukusta (2016), Kamata and Misui (2015). Concurrently, the number of domestic clients increased in the reporting period.…”
Section: Resultsmentioning
confidence: 99%